Surgical and oncological outcome of total laparoscopic radical hysterectomy versus radical abdominal hysterectomy in early cervical cancer in Singapore - Timothy Yong Kuei Lim; Krystal Koh Miao Lin; Wai Loong Wong; Ieera Madan Aggarwal; Philip Kwai Lam Yam (Wolters Kluwer Medknow Publications, 2019)
Introduction: The Wertheim's radical abdominal hysterectomy (RAH) has been the traditional surgical approach for operable Stage IB cervical cancer in Singapore whereas total laparoscopic radical hysterectomy (TLRH) was introduced only in 2009. In this study, we aimed to compare the long-term surgical outcome between the two routes of surgery in our center. Methods: This is a prospective study performed in a single large tertiary institution in Singapore. Inclusion criteria included surgically fit patients with early cervical cancer and no radiological evidence of regional or distant metastases. Results: From November 2009 to December 2014, 51 TLRHs and 85 RAHs were performed. Median blood loss in the TLRH group was significantly lower than in the RAH group (300 vs. 500 mL; P = 0.002) as was median hospital stay (5 vs. 6 days; P = 0.001). Operative time was significantly higher in the TLRH group (262 vs. 228 min; P < 0.001). There was no significant difference in bladder recovery. Intraoperative complications were encountered in 2 (3.9%) TLRH patients and 1 (1.2%) RAH patient. Postoperative complications occurred in 3 (5.9%) TLRH patients and 8 (9.4%) RAH patients. With a median follow-up of 117 (range 1.6-314.6) weeks in the TLRH group and 143.3 (range 0.4-304.7) weeks in the RAH group, 9 (17.6%) TLRH patients and 7 (8.2%) RAH patients had recurrence. There was no significant difference in the overall 3-year survival between the TLRH group and the RAH group for tumor size ≤2 cm (100.0% vs. 97.0%; P = 0.37). However, there was a trend toward lower survival for the TLRH group for tumor size >2 cm (61.9% vs. 85.4%; P = 0.06). Conclusion: The results of our study suggest that with appropriate patient selection, TLRH can be a safe and effective procedure for the management of early cervical cancer in Singapore, especially in women with small tumors ≤2 cm but should be used with caution in women with larger tumors.